ANALISIS RATIO LIKUIDITAS DAN SOLVABILITAS PADA TOKO SURYA BARU SIBOLGA - Sri Ulina Tarigan; Zafril Abdi Nasution; Mhd. Shafwan Koto (CV. ALIM'SPUBLISHING, 2023)
The purpose of this research is to find out what are the current liquidity ratios, solvency ratios and general ratios in an effort to improve the company's financial performance. The population of this study is the 2019-2021 Financial Statements of Toko Surya Baru Sibolga. The data collection method used is to use library research methods. The type of data used in this research is secondary data in the form of annual reports. The data analysis method used is descriptive analysis which aims to analyze data by describing or describing data using measurements of liquidity ratios (current ratio, quick ratio and cash ratio) and solvency ratios (debt to asset ratio, debt to equity ratio and long term debt to equity ratio). The results of the analysis are as follows (1) the liquidity ratio, according to the calculation of the average for 2019-2021, the current ratio is 188.27%, the quick ratio is 47.48%, and the cash ratio is 28.02%, indicating unfavorable conditions , because the resulting ratio is too low, especially the quick ratio and cash ratio, the company is advised to optimize its current assets, by expanding the business and suppressing the collection of uncollected company receivables. (2) the solvency ratio, according to the calculation of the average 2019-2021 debt to asset ratio, is 22.17%, the debt to equity ratio is 28.67%, and the long term debt to equity ratio is 11%, indicating the condition a good company, the company is expected to maintain financial performance so that the solvency ratio remains at the internal average because the smaller the ratio, the better the company's financial performance